PENINGKATAN KAPASISTAS TEKNOLOGI DAN NILAI TAMBAH PRODUK LIMBAH SABUT KELAPA KELOMPOK PELESTARI LINGKUNGAN BUIH MUARA DESA SUNGAI KUPAH - Fitri Imansyah; Ivan Sujana; Noveicalistus H. Djanggu (Universitas Mataram, 2023)
Pelestari Lingkungan Buih Muara group is capable of producing round peeled coconut fruit and organic fertilizer from coconut husk waste. Currently, the partner sells coconut fruit commodities at fluctuating prices based on prevailing market rates. Meanwhile, the organic fertilizer processed from coconut husk waste is sold at a price of Rp. 10,000 per 20 Kg sack. Despite the substantial potential of coconut husk waste, it hasn't been optimally utilized. The solution provided involves disseminating the results of the Community Partnership Empowerment Program (PKM) through the provision of technological product grants: a coconut husk sorting machine and a processing machine, along with providing management and entrepreneurship training. The Community Partnership Empowerment activities are implemented using a participatory method where the success of the process depends on the active participation of partners. The dissemination of technology and the enhancement of technology utilization skills and business management are carried out together with the community as an integral part of the empowerment efforts. The dissemination within the community has yielded positive results, where the coconut husk sorting machine functions optimally, separating cocofiber and cocopeat effectively, which can be used as raw materials for derivative products. From 1 kg of raw material, the sorting machine separates 60% cocofiber and 40% cocopeat. The pressing machine operates at its maximum capacity in processing cocopeat into marketable products. Entrepreneurship management training has broadened the community's knowledge and skills in managerial activities. By utilizing the sorting and pressing machines, the partners are able to produce cocopeat and cocofiber products in various desired forms by consumers. There has been an increase in the market value of the final products derived from coconut husk waste.